Management of Velopharyngeal Insufficiency in Velocardiofacial Syndrome - Manochiopinig, Sriwimon; Chuangsuwanich, Apirag; Veeravuthipakorn, Apisit (Siriraj Medical Journal, 2003)
This report presents an analysis of the treatment of a patient with velocardiofacial syndrome. The patient had a cleft palate and an articulation disorder with hypernasal speech. The cleft palate repair was successful but the post-operative course was complicated by velopharyngeal insufficiency. Thus, further management including reassessment and treatment for better speech quality was required.